(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study aims to investigate the influence of social media usage on self-compassion in adolescents by employing a quantitative methodology. Often leading to a decrease in self-compassion and comparisons, social media's ubiquitous impact shapes people's view of their mental health as well as their self. Using a methodical questionnaire & both primary and secondary sources, data were gathered from 410 adolescents in Hissar, Haryana, & Ahmedabad, Gujarat. The researchers used the Social Media Addiction Scale and the Self-Compassion Scale to gauge the degrees of self-compassion and the degree of social media usage. The results imply a modest positive correlation (R = 0.302) between self-compassion and addiction to social media, which helps to explain 9.1% of the variability. The statistical relevance (F = 40.903, p <.001) of the model shows how social media influences self-compassion. Social media can improve social ties and speed learning; but it can also encourage negative self-comparisons and addiction, which would affect teenagers' mental health negatively. In order to minimize negative consequences, the study emphasizes the need to encourage healthy social media practices and self-compassion. Additional study is needed to look into a range of settings and characteristics in order to build more effective support and intervention systems for teenagers in the digital era.